Transformations of gold nanoparticles investigated using variable temperature high-resolution transmission electron microscopy. - Young, N; Huis, v; Zandbergen, H; Xu, H; Kirkland, A (2010)
Recently designed advanced in-situ specimen holders for transmission electron microscopy (TEM) have been used in studies of gold nanoparticles. We report results of variable temperature TEM experiments in which structural transformations have been correlated with specimen temperature, allowing general trends to be identified. Transformation to a decahedral morphology for particles in the size range 5-12nm was observed for the majority of particles regardless of their initial structure. Following in-situ annealing, decahedra were found to be stable at room temperature, confirming this as the equilibrium morphology, in agreement with recently calculated phase diagrams. Other transitions at low temperature in addition to surface roughening have also been observed and correlated with the same nanoscale phase diagram. Investigations of gold particles at high temperature have revealed evidence for co-existing solid and liquid phases. Overall, these results are important in a more precise understanding of the structure and action of catalytic gold nanoparticles and in the experimental verification of theoretical calculations.